Factor IX‐deficient plasma spiked with N9‐GP behaves similarly to N9‐GP post‐administration clinical samples in N9‐GP ELISA and FIX activity assays. (30th April 2015) - Sørensen, M. H.; Andersen, S.; Ezban, M.
<x xml:space="preserve">Abstract</x> Introduction: Evaluation of assay performance with new modified coagulation factors, such as N9‐GP, may require testing of different assays and assay conditions. Validation of assays used for clinical monitoring of haemophilia B patients is challenging due to limited availability of blood samples from patients exposed to these new agents. Aim: The aim of the study is to investigate correlations between assays measuring N9‐GP concentration and factor IX (FIX) activity, and to evaluate whether in vitro FIX‐deficient plasma samples spiked with N9‐GP and in vivo post‐administration samples from patients exposed to N9‐GP perform similarly in these assays. Methods: In vitro samples, prepared by adding N9‐GP to FIX‐deficient plasma, were compared to samples from haemophilia B patients participating in the phase 3 paradigm 2™ clinical trial (in vivo samples), in assays measuring N9‐GP concentration (ELISA) and FIX activity (one‐stage clotting assay and chromogenic assay). The results of the FIX activity assays and ELISAs were compared and analysed to determine the similarity between the in vitro and in vivo sample analyses. Results: Regression analysis demonstrated a linear relationship between N9‐GP concentration and FIX activity. Furthermore, there was no significant difference between the regression lines for the in vitro and in vivo sample analyses. Conclusion: The one‐stage clot assay using SynthAFax and the chromogenic assay show promise for use in measuring FIX activity in haemophilia B patients treated with N9‐GP. Since in vitro and in vivo samples performed similarly in these assays, N9‐GP‐spiked FIX‐deficient plasma could be used as controls in routine measurements of N9‐GP activity in haemophilia B patients.